Digitalization and Digital Transformation and Adoption in the Public Administration during the Covid19 Pandemic Crisis - Xanthopoulou, Panagiota; Plimakis, Sifis (European Scientific Journal, ESJ, 2021)
The objective of the study is to find the key organizational factors that impact on digital transformation projects, creating thus a social value especially during the current pandemic crisis where many changes have been made in the ways that organizations operate. An interdisciplinary approach was used and comparison among selected European Union countries where digital governance has been applied to public-to-citizen transactions. A quantitative survey was also conducted by distributing online questionnaires to middle and senior executives of public organizations in Greece. A total of 151 questionnaires were answered and their analysis was performed using the SPSS statistical tool. The results showed that the internal factors that influence the adoption of digital governance and its successful implementation include the technological factors that compose the quality of services and mainly the organizational ones such as training and evaluation of human resources, leadership, organizational strategy, and the creation of digital culture.